Difficulties of Learning Endocrinology: Case Study of ENS Tetouan Students in Morocco - Oumaima Azzi; Jawhar Laamech; Rachid Janati-Idrissi; Rajae Zerhane (CV. Literasi Indonesia, 2023)
This study was conducted in the Ecole Normale Supérieure in Tetouan to detect the major difficulties that Moroccan students encounter in their learning of endocrinology and hormonal communication. To do this, we used semi-directive interviews to receive the opinions of these students in their learning of this subject. The final results of this survey have allowed us to identify the following difficulties according to the students: the inability to memorize the number of hormones, the complexity of the notions of endocrinology, the absence of material for practical work, the lack of supervised work sessions and the insufficiency of the time allocated to this subject. In conclusion, it turned out that the best way to help these students in their learning of endocrinology is to offer them a learning environment based on the diversified use of information and communication technologies. In other words, the well-thought-out use of tools such as digital animations could significantly increase the number of practical exercises to be performed.